Pemahaman Nilai-Nilai Agama Dalam Perspektif Hijabers Di FKIP Universitas Jember - Bakrian, Olivia Ognesti Putri (Pendidikan Islam Pascasarjana IAIN Jember, 2022)
Religion is a teaching from God that contains the order and guidance of faith and worship as a way of life for humans to manage their relationship with God, relationships with fellow humans, and relationships with the universe. with all the consequences in it, believe in the heart, declare it verbally, and realize it in action. UNEJ Jember is a campus that has been designated as the 14th-ranked research institute in Indonesia and has A accreditation. This study aims to describe the understanding of religious values ​​from the perspective of hijabers students at (FKIP Universitas Jember) which has been focused on. the perspective of hijabers students at FKIP, State University of Jember. Third, how is the understanding of moral values ​​from the perspective of Hijabers students at FKIP, Jember State University? Research In this study uses a qualitative approach, the type of case study research. Data collection techniques using participant observation, semi-structured interviews, and documentation of research informants are FKIP UNEJ Jember students and lecturers of validity used in this study by triangulation of sources. The findings of this study indicate that (1) religion is the most important thing in human life because religion is a motivation for life and life and is a tool for self-development and control. Therefore, religion needs to be known, understood, and practiced by humans so that it can become the basis of personality that can become a complete human being. (2) The results of this study indicate that most of the female students studying at UNEJ, especially at FKIP Jember, are already wearing the hijab, although many there are various variations of the hijab that students wear. Some are by Islamic sharia. The hijab that is worn by sharia is a wide veil that covers the chest. And some students wear hijabs in contemporary fashion styles with pashmina hijabs and mix and match with culottes, following the OOTD hijab. present time.